Signal Enhancement and Interference Reduction with Minimum-Variance Distortionless Response Algorithm Using MATLAB and GNU Radio Simulations - Tuan-Khanh Nguyen; Nguyen Do Nguyen; Huy Quang Nguyen; Khang Thai Viet Nguyen (Engineering Proceedings)
We improved signal reception by minimizing interference in dynamic communication environments with a minimum-variance distortionless response (MVDR) algorithm. The conditions of the MVDR algorithm were simulated using MATLAB and GNU Radio to enhance its capabilities in noise and interference suppression. Through a MATLAB simulation, the adaptive beamforming performance of MVDR was examined and compared with that of conventional beamforming techniques to identify the advantages of beam steering for obtaining the desired signals. MVDR was effective in interference reduction and the improvement of signal clarity, with superiority over conventional approaches in cases with complex interference patterns. Based on the results of the MATLAB simulations, GNU Radio was used in a complete software-defined radio (SDR) environment that enabled the replication of real-world conditions to study MVDR. We simulated real-world applications by integrating GNU Radio to ensure the robustness and adaptability of the algorithm in live signal processing. The results from these two simulations prove the potential of MVDR as a strong dynamic interference suppressor that enables superior signal reception. The results enable the implementation of the MVDR algorithm in communication systems.